La madera de Casuarina equisetifolia L., química e índices de calidad de pulpa - Villaseñor Araiza, Julio César; Rutiaga Quiñones, José Guadalupe (Instituto de Ecología, A.C., 2016)
The content of holocellulose, alfacellulose, lignin, ash, and extractives in cold water, hot water and ethanol-benzene was determined in sapwood and heartwood of Casuarina equisetifolia L. according to ASTM standards. The heartwood of casuarina wood has a greater alfa-cellulose, ash and extractives content than does its sapwood. The contents of lignin and holocellulose are similar in both samples.Fibrous material was prepared by the rapid method with a mixture of nitric acid, acetic acid, lactic acid and glycerine in equal parts. The fibers in this material were measured with a microscope and with the obtained data the indices for stiffness, flexibility, Peteri coefficient and Runkel ratio were calculated. The fibers of casuarina wood have a thick wall cell and according to the pulp index quality they are classified as regular for paper, wuith a IV quality grade.